Dairy industry restructuring - Schwarzweller, Harry K.; Davidson, Andrew Parks (Research in rural sociology and development ;, 2000)
This volume focuses on the 'dairy problem', a complex issue that relates directly to the agricultural debate of the past two decades and that concerns the socioeconomic well-being and life-chances of many farm families and rural communities in most western societies. Dairy industry restructuring is being affected by formidable forces of change: the withdrawal of government protections and price support mechanisms; the explosion of new technologies; the globalization of markets; the rising power of food processors; and the associated discontinuities of modern life. From studies in North America, Europe and Australia, the 16 articles included in this volume examine various aspects about the reshaping of this troubled industry.